Acute Coronary Syndrome in a Young Patient with Dual Mechanical Valves and Therapeutic International Normalized Ratio - A Rare Occurrence - Goel, Ridhima; Singhal, Chinar; Singhal, Chinar; Bhate, Sameer (Indian Journal of Case Reports, 2016)
Patients of valvular heart disease treated with mechanical valve replacement are required to be on lifelong medication with anticoagulants. Complications may arise when adequate International Normalized Ratio (INR) control is not maintained, leading to thromboembolic events, but very few cases have been reported where these complications arise despite therapeutic INR control. We, here, highlight a case of rare fatal complication of Acute Coronary Syndrome in a one month postoperative patient of Dual Mechanical Valve Replacement with therapeutic INR, which evaded correct diagnosis due to unawareness on the part of the treating team of physicians.